High Endothelial Venules and Lymphatic Vessels in Tertiary Lymphoid Organs: Characteristics, Functions, and Regulation - Ruddle, Nancy H. (Frontiers in Immunology, 2016)
High endothelial venules (HEVs) and lymphatic vessels (LVs) are essential for the function of the immune system, by providing communication between the body and lymph nodes (LNs), specialized sites of antigen presentation and recognition. HEVs bring in naïve and central memory cells and LVs transport antigen, antigen presenting cells, and lymphocytes in and out of LNs. Tertiary lymphoid organs (TLOs) are accumulations of lymphoid and stromal cells that arise and organize at ectopic sites in response to chronic inflammation in autoimmunity, microbial infection, graft rejection, and cancer. TLOs are distinguished from primary lymphoid organs-the thymus and bone marrow, and secondary lymphoid organs (SLOs)-the LNs, spleen, and Peyer’s patches, in that they arise in response to inflammatory signals, rather than in ontogeny. TLOs usually do not have a capsule, but are rather contained within the confines of another organ. Their structure, cellular composition, chemokine expression, and vascular and stromal support resemble SLOs and are the defining aspects of TLOs. T and B cells, antigen presenting cells, fibroblast reticular cells and other stromal cells and vascular elements including HEVs and LVs are all typical components of TLOS. A key question is whether the HEVs and LVs play comparable roles and are regulated similarly to those in LNs. Data are presented that support this concept, especially with regard to TLO HEVs. Emerging data suggest that the functions and regulation of TLO LVs are also similar to those in LNs. These observations support the concept that TLOs are not merely cellular accumulations, but are functional entities that provide sites to generate effector cells, and that their HEVs and LVs are crucial elements in those activities.